50 Years after the fury of apu Huascarán - Robles Mendoza, Román (2021)
This work recounts the memory of the events that occurred as a result of the earthquake that shook the department of Ancash on May 31, 1970. We make a summary account of the sinister city of Huaraz and the terrifying flood that buried Yungay. With the survivors of this telluric phenomenon, the central government encouraged the emigration of families affected to the Colonization of Tingo María-Tocache-Campanilla. The story concludes with the presentation of the economic and social results of the Ancash settlers settled in Nuevo Paraíso and Santa Lucía.